Influência local com procura "forward' em modelos de regressão linear - Mamani Bustamante, Juan Pablo (Universidade Federal de São Carlos, 2015)
The identification of influential and/or atypical observations in a data set is known as a part of the diagnostic analysis. One of the purposes of the diagnostic analysis is to verify the robustness of a statistical model, as the non-identification of influential observations can affect the analysis or may cause the obtainment of incorrect results. The most commonly used methodology for the diagnostic of influential observations in regression models are the global influence (Belsey et al., 1980). Cook (1986) introduced a general method to evaluate the local influence of small perturbations in the statistical model or in the data set using different perturbation schemes. As a complement to the techniques of detection atypical observations, it is proposed the forward search procedure by Atkinson e Riani (2000), which is a methodology to detect the masked atypical observations in a data set. In this work we propose the use of the local influence approach together with the forward search to obtain the masked influential observations in linear regression models.
Keywords: Estatística; Influência local; Procura forward; Curvatura normal conformal; Modelos de regressão; Gráfico de influência; Diagnostic methods; Regression model; Local influence; Influence graphs; Normal curvature; Conformal normal curvature; Forward search; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA